2020
DOI: 10.1017/s0960258520000069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and moist conditions on seed dormancy cycling of two sympatric limestone species, Begonia guishanensis and Paraisometrum mileense, in southern China

Abstract: AbstractInformation about seed dormancy cycling and germination in relation to temperature and moisture conditions in the natural environment is important for the conservation and restoration of rare species, including Begonia guishanensis and Paraisometrum mileense, two sympatric perennial limestone (karst) species. Dry afterripening (DAR) and wet and dry (WD) cycles at 15/5 and 25/15°C as well as moist chilling (MC) at 15/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…seeds from humid and semi‐humid areas of grassland, forest edge and meadow and found that seed GP decreased under dry/wet cycles. Seed germination of Begonia guishanensis in Karst mixed forest was reduced by dry/wet cycling compared to a dry treatment (Hu et al ., 2020). These researchers suggested that this was a dormancy adaptation of seeds to adverse germination conditions (Downs & Cavers, 2000; Hu et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…seeds from humid and semi‐humid areas of grassland, forest edge and meadow and found that seed GP decreased under dry/wet cycles. Seed germination of Begonia guishanensis in Karst mixed forest was reduced by dry/wet cycling compared to a dry treatment (Hu et al ., 2020). These researchers suggested that this was a dormancy adaptation of seeds to adverse germination conditions (Downs & Cavers, 2000; Hu et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Seed germination of Begonia guishanensis in Karst mixed forest was reduced by dry/wet cycling compared to a dry treatment (Hu et al ., 2020). These researchers suggested that this was a dormancy adaptation of seeds to adverse germination conditions (Downs & Cavers, 2000; Hu et al ., 2020). In addition, dry/wet cycling may damage organelles and the osmotic function of cell membranes, further leading to leakage of solutes and low molecular weight metabolites in cells (Bewley, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation